Efektivitas Model Discovery Learning pada Mata Pelajaran Instalasi Penerangan Listrik - Tomo, Yori; Aswardi, Aswardi (Minangkabau Scholar Institute, 2020)
This study aims to look at the effectiveness of the model learning discovery on Electric Lighting Installation with Basic Competencies component mounting procedure applying electrical installation of small industrial buildings in SMK N 2 Sijunjung. The type of this research is a Pre-Experiment design with research design used is The One Shot Case Study. Based on the results that the percentage of classical completeness student attitudes 87%, student skills 84%, and 87% of students knowledge. After analyzed, the student learning outcomes achieved by students' attitudes category of